Perspectives of unaccompanied refugee children, their foster carers and guardians on placement success: Which factors predict multi-informant discrepancies?. (September 2021) - Rip, Jet; Hasami, Selsela; Post, Wendy; Zijlstra, Elianne; Knorth, Erik J.; Kalverboer, Margrite
Highlights: Multi-informant discrepancies (child, carer, guardian) were studied in foster care. High average placement success is associated with low informants' discrepancies. Discrepancy in child and fostering factors predicts discrepancy in success scores. Low average placement success may co-exist with placement breakdown. Abstract: This study examined multi-informant discrepancies (between child, carer, and guardian perspectives) regarding placement success of 39 foster placements, as well as possible factors associated with these discrepancies. We also examined whether these discrepancies in placement success at baseline measurement (T0) are related to placement breakdown at second measurement (T1). The results showed that when placements are rated with a high average placement success score (looking at child-carer and child-guardian dyads), the child and carer, as well as the child and guardian generally agree on the success of the foster placement, showing low discrepancy. In contrast, placements with a low average score on placement success show large discrepancies between the perspectives, which may also lead to breakdown. Results of the multilevel analyses showed that discrepancies regarding placement success were mainly associated with differences in perspectives regarding fostering factors (i.e., quality of the caregiving environment, child-carer and child-guardian relationship) and child factors (i.e., conduct problems, emotional problems). The results indicate that children and their carers or guardians disagree more on the success of the placement if they disagree on the quality of the caregiving environment, the child's conduct and emotional problems, and the quality of the child-carer and child-guardian relationship. The outcomes of our study might be especially helpful for guardians in shaping their guidance practices.